RELATIONSHIP BETWEEN SCHOOL PHYSICAL ENVIRONMENT AND STUDENTS’ ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN ONITSHA SOUTH LOCAL GOVERNMENT AREA OF ANAMBRA STATE (UNIZIK Journal of Educational Management and Policy, 2026)
The purpose of the study was to investigate the relationship between school physicalenvironment and students’ academic performance in public secondary schools in Onitsha SouthLocal Government Area of Anambra State. Two research questions guided the study and twonull hypotheses were tested at 0.05 level of significance. The correlational survey researchdesign was adopted for the study. The population for the study comprised all the 641 SeniorSecondary School (SSS II) students in the six public secondary schools in Onitsha South LocalGovernment Area of Anambra State. The sample size comprised of 160 respondents drawn usingproportionate stratified random sampling technique. The instrument for data collection was aresearcher-structured rating scale titled: “School Physical Environment Rating Scale (SPERS)and Academic Performance Test (APT). The SPERS was validated by three experts. The expertsmade adjustments to the item statements in terms of statements clarity. The instrument wassubjected to a pilot test on 20 students in Onitsha North LGA. The reliability coefficients valuesof 0.81 for school site and 0.84 school infrastructural facilities were obtained respectively.Pearson Product Moment correlation was used to answer the research questions and in testing thehypotheses. Findings of the study revealed among others that school site has a moderate positiveand significant relationship with students’ academic performance in public secondary schools inOnitsha South LGA. Findings of the study further revealed that school site has a high positiveand significant relationship with students’ academic performance in public secondary schools inOnitsha South LGA. It was therefore recommended among others that policy makers shouldprioritize funding for school infrastructure improvements to enhance student performance,particularly in underserved areas with suboptimal school sites.
Keywords: Academic Performance, School, Physical Environment